2020
DOI: 10.12688/f1000research.26072.1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal lipid levels in pregnant women without complications in developing risk of large for gestational age newborns: a meta-analysis

Abstract: Background: Circulating into foetal circulation across the placental barrier, abnormal maternal serum lipids predispose neonates to metabolic dysfunction and thereafter affect the steroid metabolism and functions of extra-embryonic foetal tissues. Methods: A systematic review was conducted by searching PubMed–MEDLINE and the Cochrane library between January 2010 and January 2020. The included studies were English case control studies that described original data on at least one raw lipid measurement during pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Research demonstrated a connection between elevated maternal triglyceride and low high-density lipoprotein cholesterol levels and large-for-gestational-age infants. [ 28 30 ] The aforementioned findings showed that changes in the metabolism of macronutrients other than glucose levels might potentially contribute to the onset of macrosomia in children. As a further extension, the GDM-HFBG group may have more metabolic issues unrelated to glucose due to greater insulin resistance or other unidentified pathways, resulting in a higher incidence of unfavorable pregnancy outcomes than the NGT group.…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrated a connection between elevated maternal triglyceride and low high-density lipoprotein cholesterol levels and large-for-gestational-age infants. [ 28 30 ] The aforementioned findings showed that changes in the metabolism of macronutrients other than glucose levels might potentially contribute to the onset of macrosomia in children. As a further extension, the GDM-HFBG group may have more metabolic issues unrelated to glucose due to greater insulin resistance or other unidentified pathways, resulting in a higher incidence of unfavorable pregnancy outcomes than the NGT group.…”
Section: Discussionmentioning
confidence: 99%
“…Among offspring born to mothers with dyslipidemia, increased birthweight, a higher risk of abnormal birth outcomes, such as macrosomia, largeness for gestational age, as well as atherosclerosis in adulthood were reported in several studies [ 116 , 117 , 118 , 119 , 120 , 121 ]. When pregnant women had VD deficiency, TG levels increased, and high-density lipoprotein cholesterol (HDL-C) levels decreased in the umbilical artery in a 425-participant study [ 122 ].…”
Section: The Relationship Of Vd Deficiency During Pregnancy and Obesi...mentioning
confidence: 99%